Resting Heart Rate, Functional Capacity and Prognosis in Heart Failure Patients: Atrial Fibrillation Versus Sinus Rhythm - Ilhão Moreira, R (2020)
Background: Higher resting heart rate (HR) is associated with lower exercise capacity and worse prognosis in patients with heart failure (HF). However, recent studies question this relationship in HF patients in atrial fibrillation (AF). We aimed to examine and compare the relationships between resting HR, exercise capacity and outcomes in HF patients in AF and sinus rhythm (SR). Methods: 282 ambulatory patients with symptomatic HF and left ventricular ejection fraction≤40% were divided according to rhythm status into SR and AF group. All patients were followed for 60 months and the combined endpoint was defined as cardiac death, urgent heart transplantation or need for mechanical circulatory support. Results: In the patients enrolled (mean LVEF 27±7%), 19.1% had AF. The composite endpoint occurred in 24.4% during follow-up. There were no differences regarding maximal effort, but AF group had lower exercise capacity. In the SR group, there was an inverse relationship between resting HR and exercise capacity (r-0.189, p 0.004). In the AF group, this relationship was reversed as higher resting HR was associated with better exercise tolerance (r 0.314, p 0.021). Regarding outcomes, patients in SR with a resting HR higher than 72 bpm had higher risk of composite outcome than those with lower resting HR (p 0.033), but this was not evident in AF patients. Conclusion: The impact of resting HR on exercise capacity and prognosis differed entirely between AF and SR, suggesting that HR control may need to be managed differently for AF and SR in HF patients.